Innovative Development of Small Entrepreneurship in Ukraine in a Changing Environment - Al-Ababneh, Hassan Ali; Liumanov, Amet; Artemchuk, Mykyta; Kolomiiets, Yevhenii; Skrylnik, Andrey; Vakulich, Maria (International Journal of Economics and Financial Issues, 2025)
The aim of the study is to assess the impact of innovative development of small businesses in Ukraine on its competitiveness in the context of economic and social changes, as well as to identify factors that affect the effectiveness of innovation strategies in small businesses. The research employed the following methods: Correlation, regression analysis, and analysis of variance (ANOVA). The study established a positive impact of state support on the financial results of enterprises, the correlation between the financial result and the state support level is 0.76. A correlation was also found between the cost of credit resources and financial indicators (correlation coefficient 0.61), as well as a moderate positive relationship between investment in innovation and profitability (0.39). The digitization index (DiGiX) showed a weak impact on the financial result (−0.07), which indicates a significant time for the payback of investment in digitalization. The study covers the period from 2017 to 2024, and it was found that state support and access to credit resources are the main factors determining the success of innovation strategies in small businesses. The results can become the basis for further development of state policies and strategies to stimulate innovation development in Ukraine.